Assessment of long-term cardiac adaptation in adult patients with type II atrial septal defect - Akito, Hiraoka (2021)
Objectives: In type II atrial septal defect (ASD) patients, the left-to-right (LR) shunt causes adaptation of the heart and circulation. The study objective was to evaluate with cardiovascular magnetic resonance imaging (CMR) the impact of LR shunt on left (LV) and right ventricular (RV) volumes, function, and myocardial strain. Methods: Thirty-five patients (42 ± 17 years, 17 male) were compared to a control group (n = 40). Cine imaging was used to calculate ventricular volumes and ejection fraction (EF), global longitudinal (GLS) and circumferential strain (GCS), and longitudinal free wall (FWS) and interventricular septal (IVS) strain. Phase-contrast imaging was used to calculate pulmonary flow to systemic flow ratio (Qp/Qs). Results: The LR shunt (Qp/Qs 2.2 ± 0.6) resulted in larger RV end-diastolic volume (EDVi) (152 ± 42 vs 82 ± 11 ml/m2 ), lower LV EDVi (72 ± 16 vs 83 ± 9 ml/m2), and higher RV/LV EDVi ratio (2.2 ± 0.5 vs 1.0 ± 0.1) than controls (all p < 0.001). Functionally, stroke volumes were larger in RV and lower in LV (both p < 0.001) with a strong trend toward lower RV EF in patients (p = 0.08). The LR shunt negatively impacted RV GLS (p = 0.03) but not RV GCS. Longitudinal IVS but not RV FWS were significantly lower in patients, i.e., p < 0.001, of longitudinal IVS. Shunt severity correlated with RV size and stroke volume, right atrial size, and pulmonary trunk diameter (all p < 0.001), but not with functional nor strain parameters. Conclusion: Long-term cardiac adaptation in ASD patients, with RV overfilling and LV underfilling, has a negative impact on systolic RV performance, a phenomenon which likely can be attributed to longitudinal dysfunction of the interventricular septum.